Utility of cystoscope sheath in percutaneous nephrolithotomy- a case report - Gali, Kasi V.; Choudhary, Anupam; Singh, Anshuman; Shah, Abhijit (International Journal of Research in Medical Sciences, 2023)
Retrieval of high-volume renal stone fragments in percutaneous nephrolithotomy (PCNL) using graspers and baskets can lead to inadvertent renal mucosal trauma and prolonged operative times. We report a case of large right renal pelvic calculus measuring approximately 5.6×4.2×4 cm, which after fragmentation posed a challenge for fragment retrieval to ensure complete stone clearance. We used flush irrigation and suction through a 17 Fr cystoscope sheath inserted into the 30 Fr Amplatz for successful retrieval of the high volume of tiny stone fragments. To our surprise, just after two cycles of flush-irrigation and suction in a duration of approximately 30 seconds, we could achieve complete stone clearance. This technique of utilizing a small caliber cystoscope sheath through a large caliber Amplatz in PCNL could help in selected cases for efficient and safe retrieval of high-volume tiny stone fragments by minimizing renal mucosal trauma, operative times and ensuring complete stone clearance.